FORMATION OF THE CONCEPT OF INFORMATION AMONG STUDENTS IN THE STUDY OF COMPUTER SCIENCE IN SECONDARY SCHOOL - Turdina А.Б.; Kerimbayev А.О.; Mukushev А.Б.; Adilbekova Б.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Information theory refers to the teaching of an interdisciplinary orientation. To date, the scientific and practical results of information theory have found wide application in computer science, mathematics, physics, linguistics and other fundamental sciences. The article describes the theoretical, practical and pedagogical aspects of the concept of information. It is established that information is a fundamental concept and its place in social and natural processes is determined. The role of the subject of computer science in the study of fundamental problems of the concept of information in the educational process of secondary and higher schools is considered. The essence and application of the Hartley and Shannon formulas are revealed. These equations are the basic equations of information theory. Based on the theory of probability, the concept of information uncertainty is given and the unit of its measurement is presented. Various scientific directions of information theory are investigated: the measurement of information values and the use of the Shannon equation in the testing process.